2007
DOI: 10.1111/j.1472-765x.2007.02167.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prebiotic oligosaccharides and trehalose on growth and production of bacteriocins by lactic acid bacteria

Abstract: Aims:  To investigate the effects of two prebiotics and trehalose on the production of bacteriocins. Methods and Results:  Four carbohydrates [dextrose, fructo‐oligosaccharides (FOS), raffinose, and trehalose] were used as the sole carbon source in a simple broth. Five bacteriocin‐producing strains of bacteria, including those producing nisin, enteriocin, and other bacteriocins, were used, and their inhibitory activities when grown on each carbohydrate were determined. The inhibitory activity assay was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…Recently, an effective enhancement of bacteriocin production was observed when FOS or trehalose was used by strains of Lactococcus and Enterococcus (8). However, studies relating to the antibacterial properties of Lb.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, an effective enhancement of bacteriocin production was observed when FOS or trehalose was used by strains of Lactococcus and Enterococcus (8). However, studies relating to the antibacterial properties of Lb.…”
Section: Discussionmentioning
confidence: 98%
“…However, the disadvantages of the yeast treatment for the purification of GOS are the incapacity of the yeast cells to remove the disaccharides, the subsequent need for elimination of these cells from the sample and the metabolic products formed during the fermentation, such as glycerol or trehalose. Nevertheless, Chen et al (2007) indicated that prebiotic fructooligosaccharides and trehalose enhanced the growth and production of bacteriocins by lactic acid bacteria, suggesting a new potential application of this mixture of carbohydrates in food preservation. Consequently, it could be of interest to further evaluate this effect on a mixture of GOS and trehalose after treatment with S. cerevisiae.…”
Section: Size Exclusion Chromatographymentioning
confidence: 97%
“…On the other hand, in the literature there are several reports on the improvement of bacteriocin production when LAB were grown in the presence of raffinose, lactulose, fructoligosaccharides, and trehalose (7,39). According to Leroy and De Vuyst (21), the conditions for production of bacteriocins are not easily predicted because the regulation of the synthesis of these antimicrobial peptides depends on complex parameters.…”
Section: H (A) and 24 H(b) Of Exposure To Bile Salts (3 Mg Mf1 Oxgallmentioning
confidence: 98%